The Role of Streptococcus pneumoniae in Community-Acquired Pneumonia - Feldman, Charles; Anderson, Ronald (Seminars in Respiratory and Critical Care Medicine, 2020)
With the notable exceptions of the United States and Canada in particular, the global burden of disease in adults due to invasive infection with the dangerous respiratory, bacterial pathogen, Streptococcus pneumoniae (pneumococcus) remains. This situation prevails despite the major successes of inclusion of polysaccharide conjugate vaccines (PCVs) in many national childhood immunization programs and associated herd protection in adults, as well as the availability of effective antimicrobial agents. Accurate assessment of the geographic variations in the prevalence of invasive pneumococcal disease (IPD) has, however, been somewhat impeded by the limitations imposed on the acquisition of reliable epidemiological data due to reliance on often insensitive, laboratory-based, pathogen identification procedures. This, in turn, may result in underestimation of the true burden of IPD and represents a primary focus of this review. Other priority topics include the role of PCVs in the changing epidemiology of IPD in adults worldwide, smoking as a risk factor not only in respect of increasing susceptibility for development of IPD, but also in promoting pneumococcal antibiotic resistance. The theme of pneumococcal antibiotic resistance has been expanded to include mechanisms of resistance to commonly used classes of antibiotics, specifically β-lactams, macrolides and fluoroquinolones, and, perhaps somewhat contentiously, the impact of resistance on treatment outcome. Finally, but no less importantly, the role of persistent antigenemia as a driver of a chronic, subclinical, systemic proinflammatory/procoagulant phenotype that may underpin the long-term sequelae and premature mortality of those adults who have recovered from an episode of IPD, is considered.
Keywords: antibiotic resistance; β-lactams; cigarette smoking; fluoroquinolones; inflammation; macrolides; persistent antigenemia; pneumococcal conjugate vaccine; vaping